Gdzie mieszka język? - Zabrocki, Władysław (Scripta Neophilologica Posnaniensia, 2020)
The article is devoted to the problems of the ontological assumptions of linguistics. It is argued that the thesis on the diversity of these assumptions goes beyond the classic positions in the dispute over language universals. The dependence of ontological assumptions on the empirically established linguistic theories is indicated.